A Study of Key Factors For Energy Policy Modelling - Obrecht, Matevž; Denac, Matjaž (Naše gospodarstvo/Our economy, 2012)
Environmental problems and high fossil fuel import dependency are core ener- gy problems facing the EU, which has therefore committed itself to increasing its share of renewable energy sources (RES) to 20% by 2020. The implementation of planned measures is usually the most challenging issue in such a situation; therefore, energy models addressing this issue were studied. Because their specificity means that their usability is limited, we developed a more general model focused on the implementation of the planned measures for the development of a more sustainable energy policy with a higher share of RES. The key factors for modelling this transition were identified and examined, and a comparative analysis of Slovenian, EU, and global energy statistics and analyzed energy mix were carried out. In addition, RES potentials were evaluated, future energy demand was forecast, and compati- bility of RES potentials and future energy demand was tested. Based on the results, two energy modelling approaches were developed.